Instruments and Perspectives of Coping with Pandemic COVID-19 in the Assessments of Medical Workers of the Kharkiv Region - Lytovchenko, Artem; Boyko, Dmytro; Baieva, Maryna; Ostapenko, Halyna (Волинський національний університет імені Лесі Українки, 2021)
Groups with special qualities in the eyes of the public can help to overcome barriers to vaccination and other anti-pandemic measures. Such groups can be opinion leaders to advance the pandemic response. One of these groups is specialized doctors. A research question: how ready are they today to act as a group opinion leader in promoting vaccinations and other responses to the pandemic? We present original data that allow us to draw the local (national) characteristics of attitudes towards measures to coping the pandemic of medical workers in Ukraine, and about their potential as an agent for informational promotion of vaccination. We used a questionnaire survey of medical workers (797 medical workers were interviewed in March-September 2021) in the Kharkiv region to collect empirical material. We focused on their assessment of the readiness to vaccinate their environment – as an indirect indicator of assessing the prospects for mass vaccination and their own ability to act as agents of promoting mass vaccination. According to the results of the survey, the social group potential of medical workers in promoting vaccination is relatively high. About half of doctors with higher education, who are included in the pandemic topics of the information space and are confident in the need for mass vaccination, can be the agent core of the information promotion of anti-pandemic tools, particularly vaccination. Центральна пробле-ма статті – перспективи, можливі канали та агенти просування протипандемічних заходів у «ковідний» період. У статті представлено дослідження колективної свідомості медичних працівників Харківської області щодо оцінок засобів і перспектив боротьби проти пандемії КОВІД-19. Вирішується дослідницьке питання про потенціал специфічних груп як агентів соціального просування вакцинації та інших протипандемічних інструментів; мета статті – охарактеризувати цей потенціал стосовно медичних працівників як особливої групи. Для досягнення мети проведено масове анкетування (n=797) лікарів та молодшого медичного персоналу. Оцінку перспектив вакцинації здійснювали за допомогою побічного індикатора – оцінки готовності до вакцинації найближчого оточення. Результати дослідження свідчать про те, що близько половини медичних працівників (із вищою освітою, включені до «ковідної» тематики інформаційного простору, упевнені в необхідності масової вакцинації) можуть становити агентне ядро, яке можна задіювати задля інформаційного просування вакцинації й інших протипандемічних заходів.
Keywords: COVID-19 pandemic; health workers; vaccination barriers; opinion leaders; vaccination readiness; 316.42:316.454:316.4.063